The reality of adolescent girls’ exposure to the dangers of the digital world in Saudi society: A study applied to a sample of middle school students in the city of Riyadh - Alnasser, Rawan Ibrahim (Journal of Humanities & Social Sciences, 2021)
This study aimed to identify the reality of adolescent girls’ exposure to the dangers of the digital world according to the classification of the UNICEF organization and to reveal the most dangerous applications for them. This study relied on the method of social survey through the sample using the questionnaire tool, and the study sample reached (402) single female students Medium in the city of Riyadh, using stratified random sampling. The results of the study revealed that content-related risks are among the most common types of risks that adolescent girls face in the digital world, followed by communication risks and then behavioral risks. The results also showed that among the applications in which adolescent girls are most exposed to the dangers of the digital world (Instagram - Twitter - Snapchat), In terms of usage, YouTube ranked first in terms of usage, followed by Snapchat, Instagram, WhatsApp, Twitter, Tik Tok, then PUBG and Fortnite. The study recommended the need to establish a specialized unit affiliated to the Communications and Information Technology Commission, which includes a number of specialists in the social, psychological and cybersecurity fields. It also includes visual and print media and celebrities of social networking sites who have an impact on the category of children and adolescents. The study also recommended the need to focus the efforts of the committee. To legalize the ethical content of information technology on the most popular websites and applications in the digital world, such as (Twitter, Instagram), by intensifying censorship and working to reduce the availability of harmful and inappropriate materials on these sites.